2016
DOI: 10.1017/s0144686x16000155
|View full text |Cite
|
Sign up to set email alerts
|

Trying to be someone you can never be again: retirement as a signifier of old age

Abstract: Work occupies a central place in identity formation. Consequently, retirement places retirees in a new reality that compels them to redefine themselves and adopt a new identity. The present article examines how retirees shape their identity in the absence of work. An interpretive analysis of in-depth interviews conducted with retirees in Israel shows that although retirement and old age are not necessarily equivalent or interconnected, the retirees themselves draw parallels between them, and at the same time a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
(86 reference statements)
0
8
0
Order By: Relevance
“…Arab society presents a hybrid conception of ageing, and the analysis of the intergenerational relations does not generate a single, complete, coherent, or consistent narrative but rather a variety of discourses taking place in space and time that can be understood in broader social contexts (Manor, 2017). It thus preserves collective values regarding the importance of family and respect for the elders.…”
Section: Discussionmentioning
confidence: 99%
“…Arab society presents a hybrid conception of ageing, and the analysis of the intergenerational relations does not generate a single, complete, coherent, or consistent narrative but rather a variety of discourses taking place in space and time that can be understood in broader social contexts (Manor, 2017). It thus preserves collective values regarding the importance of family and respect for the elders.…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxically, spending time with older people in one's own age group contributes to self-ageism. Furthermore, research findings have indicated that older people who live with other older people tend to perceive themselves as younger than their chronological age and belonging to a younger age group (Manor 2017). It is, remarkably, older people themselves who formulate ageist positions toward their peers while denying their own age and treating the group to which they belong stereotypically (Bodner 2009;Gamliel & Hazan 2006;Manor 2017).…”
Section: Self-ageism and Social Identity: A New And Foreign Concept Imentioning
confidence: 99%
“…Furthermore, research findings have indicated that older people who live with other older people tend to perceive themselves as younger than their chronological age and belonging to a younger age group (Manor 2017). It is, remarkably, older people themselves who formulate ageist positions toward their peers while denying their own age and treating the group to which they belong stereotypically (Bodner 2009;Gamliel & Hazan 2006;Manor 2017). Support for this argument that older people hold negative views of their own age group, despite being completely unfamiliar with the word ageism, was also found in other studies (Minichiello et al 2000).…”
Section: Self-ageism and Social Identity: A New And Foreign Concept Imentioning
confidence: 99%
“…Silver 24 showed that people in executive positions could perceive retirement as an unwanted change forced by social pressure because work provided them with a sense of productivity, networking opportunities, significant fulfillment, and personal satisfaction they did not want to lose. Manor 22 pointed out that the moment of retirement marked the transition to old age and that participants in her study strongly rejected the idea of becoming old. Additionally, work is also a crucial aspect of self‐identity for people with dementia, as demonstrated by Cohen‐Mansfield et al 25 .…”
Section: Introductionmentioning
confidence: 98%
“…Narrative identity is shaped by various social roles we undertake throughout our lives. For adults, work is one of the most important sources of identity and social affiliation 21,22 . Many studies have shown that work continues to be an essential aspect of self‐identity even after retirement.…”
Section: Introductionmentioning
confidence: 99%